Genealogy of Inclusive Education in Nepal - Neupane, Nam Raj; Adhikari, Narayan Prasad; Kafle , Basu Dev (Interdisciplinary Research in Education, 2025)
This study aims at exploring historical and transformative perspective of education in terms of inclusion in Nepal. The study further deals with paradigm shifts in education from the inclusion perspective. This is a qualitative research with systematic investigation of the developmental history of inclusive education in Nepal. Secondary data were collected from document analysis, library search, reference materials, and internet surfing. The study found out that inclusion concept in Nepal was developed basically from discourse on educational opportunities for children with disabilities. The provision of education for children with disabilities was incorporated in special education policies. The changing paradigm in education took place along with changing political landscapes of Nepal. The education policies of Nepal are also influenced by international contexts and policy provisions which are acting as source and also the pressurizer for developing and revising national policies.